Analysis of customer loyalty towards Askco Sdn. Bhd. / Hazwani Amira Abdul Jamil - Abdul Jamil, Hazwani Amira (2018)
In this study, the reaseacher has learn more about marketing plan which every company needs it in order to achieves their every mission to get customers remain loyal to their services. These days, there are many business consultation in Selangor which make as Askco Sdn Bhd one of their competitors too. By that what the researcher has seen are the lack of management data and not knowing what customer wants for their business. The problem of Askco Sdn Bhd cannot be solved simply by providing more services and spending more on activities that related to customers' businesses. There is an urgent need for innovation, for better understanding of the current and potential role of activities for customers which concern the company. Thus, this research aim is to study analysis of customer loyalty towards Askco Sdn Bhd. It specifically studies on Askco Sdn Bhd own clients to make their customers remain loyalty to their services. This research is based on data obtained from survey questionnaire. The data was analysed to evaluate and determine the tangible, reliability, responsiveness and assurance with customers loyalty. The research suggested that successful customer loyalty towards Askco Sdn Bhd as linked to reliability. The result of the study also suggested that a reliability is needed for the customer loyalty in order to remain their customers and satisfied with the services provided by Askco Sdn. Bhd. It hope that the study can contribute to the improvement of Askco Sdn Bhd services and expand their business in Shah Alam.